Severe phimosis leading to obstructive uropathy in a boy with lichen sclerosus - Sancaktutar, Ahmet Ali; Kilincaslan, Huseyin; Atar, Murat; Soylemez, Haluk; PENBEGÜL, NECMETTİN; BOZKURT, YAŞAR; Tepeler, Abdulkadir (My University, 2012)
Lichen sclerosus (LS) is a chronic, inflammatory condition which commonly involves the anogenital skin. This condition may affect the foreskin, glans, frenulum, meatus and urethra in males. It manifests itself with voiding symptoms. Obstructive uropathy is an extremely rare clinical presentation in childhood. This study reports the case of a 13-year-old boy presenting with obstructive uropathy due to LS and reviews the published data on the diagnosis, management and follow-up of this condition.